Implementation of Disaster Preparedness in Hospitals by Emergency Department Nurses - Calisanie, Nyayu Nina Putri; Ramdani, Ramdani; Nuriyah, Musopi (STIKep PPNI Jawa Barat, 2024)
Aims: The purpose of this study is to determine the preparedness of emergency room nurses in handling disasters in hospitals. Method: This study employs a qualitative research design, utilizing a single case study that focuses on the implementation of disaster preparedness by emergency room nurses in hospitals. The subjects of this case study are two nurses who meet the inclusion criteria: they have attended disaster preparedness training, work as emergency room nurses, have been part of the hospital disaster team for at least five years, and are considered reliable and competent sources of data related to the research objective. Purposive sampling was used to select the participants, and data was collected through in-depth interviews guided by an interview protocol. Results: Four themes were identified: disaster preparedness, the organizational structure of disaster management functions and tasks, patient grouping, and the communication of clear, effective information along with coordination among medical personnel. Conclusion: The study found that implementing preparedness among emergency room nurses in disaster management is crucial to ensure a prompt and effective response in emergency situations.